Del rouge delator y la catacresis en el discurso identitario de La esquina es mi corazón, de Pedro Lemebel (In Memoriam) - Ostria Reinoso, Olga (2015)
The following analysis proposes an interpretation of the urban chronicles La esquina es mi corazón written by Pedro Lemebel as an identitarian-literary discourse: poetic proposal that configures, from the particular textual dimension of the urban chronicle, a discourse which is generic in terms of sexual context and is also anti national. Making an attempt to dialogue with previous studies, this work focuses in two aspects not well attended by the critics but that are profoundly meaningful for the lemebelian production, and which here is conceived as his travesty poetics: the symbolism of denunciation and the catachresis resource. Cultural discourse and artistic configuration find in signs of contradiction a bridge by which this reading attempts to link society and literary imagination.